Protein sustained release from isobutyramide-grafted stellate mesoporous silica nanoparticles - Joëlle Bizeau; Alexandre Adam; Clémence Nadal; Grégory Francius; David Siniscalco; Matthias Pauly; Sylvie Bégin-Colin; Damien Mertz (Elsevier, 2022)
Proteins are great therapeutic candidates as endogenous biomolecules providing a wide range of applications. However, their delivery suffers from some limitations and specifically designed delivery systems having an efficient protein anchoring and delivery strategy are still needed. In this work, we propose to combine large pore stellate mesoporous silica (STMS) with isobutyramide (IBAM), as a "glue" molecule which has been shown promising for immobilization of various biomacromolecules at silica surface. We address here for the first time the ability of such IBAM-modified NPs to sustainably deliver proteins over a prolonged time. In this work, a quantitative loading study of proteins (serum albumin (HSA), peroxidase (HRP), immunoglobulin (IgG) and polylysine (PLL)) on STMS@IBAM is first presented using three complementary detection techniques to ensure precision and avoid protein quantification issues. The results demonstrated a high loading capacity for HSA and HRP (≥ ca. 350 μg.mg−1) but a moderate one for IgG and PLL. After evaluating the physicochemical properties of the loaded particles and their stability over scaling-up and washings, the ability of STMS@IBAM to release proteins over prolonged time was evaluated in equilibrium (static) and flow mimicking (dynamic) conditions and at different temperatures (25, 37, 45 °C). Results show not only the potential of such "glue" functionalized STMS to release proteins in a sustained way, but also the retention of the biological activity of immobilized and released HRP, used as an enzyme model. Finally, an AFM-force spectroscopy study was conducted to decipher the interactions between IBAM and proteins, showing the involvement of different interactions in the adsorption and release processes.